PENGEMBANGAN HANDOUT DISERTAI PETA KONSEP BERGAMBAR PADA MATERI SISTEM PERNAPASAN UNTUK SISWA SEKOLAH MENENGAH PERTAMA (SMP) - Geni, Puty Lenggo; Sudirman, Sudirman; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The factor of environment in learning process are needed attetion by theÂ teacher is some learning media, that can make easier student for learning process. One of the effort that should be to do by the teacher to make student easier in learning proses is preapere learning media. Base of observation and result of interview with one of biology teacher at SMP N 30 PadangÂ that say in the learning teacher use material teachesas tesk book and LKS in the marked. Related didnât have handout so Â it can be developed the handout with picture consept map of respiration system in biology for junior high school. This research was developmental research which was used 4-D models, it consists four steps but that limited become 3 steps were define,design and develop. Practicality test by 2 teachers and 37 students at class VIII of junior high school. Analisys data by percentage technique and process of descriptive. The result of validity handout with picture concept map in by validator showed that handout was very valid with 90,62%. The result of practicality handout by the teachers showed that this handout with criteria very practice 90,72% and the result practicality by students showed that this handout in criteria practice was 82,50 %. It can be concluded that handout with picture concept map of respiration system it was valid and practice.Â Â